2017
DOI: 10.1017/s175173111600269x
|View full text |Cite
|
Sign up to set email alerts
|

A 3-week feed restriction after weaning as an alternative to a medicated diet: effects on growth, health, carcass and meat traits of rabbits of two genotypes

Abstract: Feed restriction after weaning is widely used in meat rabbit farms to promote health and reduce mortality, but this practice impacts negatively on rabbit growth and slaughter performance. This study compared a 3-week post-weaning feed restriction with ad libitum medicated feeding, evaluating effects on feed intake, growth, health, carcass and meat quality of rabbits of two genotypes: Italian White pure breed and Hycole hybrid × Italian White crossbred. A total of 512 rabbits at 36 days of age, of both sexes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 24 publications
13
26
0
Order By: Relevance
“…In terms of meat quality characteristics, tenderness is the most important factor for consumers. Feed restriction did not affect the meat toughness and was consistent with Carrilho et al (2009), Alabiso et al (2016) and our previous results (Chodov a et al 2016). The cooking loss is one of the parameters by which the water holding capacity is expressed, and there was no effect of feeding regime on cooking loss, which corresponds with the observations of .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In terms of meat quality characteristics, tenderness is the most important factor for consumers. Feed restriction did not affect the meat toughness and was consistent with Carrilho et al (2009), Alabiso et al (2016) and our previous results (Chodov a et al 2016). The cooking loss is one of the parameters by which the water holding capacity is expressed, and there was no effect of feeding regime on cooking loss, which corresponds with the observations of .…”
Section: Discussionsupporting
confidence: 91%
“…Our feeding regime did not affect the dressing out percentage, as was also observed by Tůmov a et al (2003,2006), Oliveira et al (2012) and Alabiso et al (2016). In contrast, the application of feed restriction at 35 days of age, one week after weaning, resulted in a lower dressing out percentage in restricted rabbits (Chodov a et al 2016).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Overall, the live weights of both the South African NZW and Phendula rabbits compared well with those reported for various breeds, breed crosses and hybrid lines in recent literature (Pascual et al, 2015;Alabiso et al, 2017;Nasr et al, 2017;Belabbas et al, 2019). However, in the absence of standardized rearing and environmental conditions, the value of these comparisons is limited.…”
Section: Discussionsupporting
confidence: 69%
“…The greater live weights for female rabbits than males of both breeds at 11 weeks old resulted from the greater ADG of females towards the end of the growth period (Figure 1), These results differed from North et al (2018a), in which no sex effect on live weight was detected for NZW from the same genetic stock. Bernardini Battaglini et al (1995), Ortiz Hernández & Rubio Lozano (2001, Yalçin et al (2006) and Alabiso et al (2017) similarly reported no sex differences in live weight or SW for a variety of genetic types. However, whereas Blasco & Gomez (1993) found no sex differences in a line selected for growth rate, females from a line selected for litter size had significantly greater live weights than males from the same line.…”
Section: Discussionmentioning
confidence: 95%